(untitled) - The World Bank in Vietnam (WB) (Ha Noi, 2011)
The World Bank (WB) Group has been a close companion to Vietnam over the last decades in support of its development path with enormous contributions not only for Vietnam's efforts to transition from a poor, low income country to a Middle-Income Country, but also supporting Vietnam to go two-thirds of the way to achieve the Millennium Development Goals as of 2010. The Government and the World Bank want to mark this event through an overall assessment of the partnership between the two sides during the history of bilateral relations of more than three decades, pointing out positive impacts of this partnership on socio-economic development and poverty reduction in Vietnam. On that basis, it will summarize the experiences and draw useful lessons for the development of the continued strategic partnership between Vietnam and the World Bank in the new stage of development of Vietnam. The report 'Vietnam World Bank: long-term companions in development' is based on research, synthesis, analysis and assessments of WB activities in Vietnam and consultations with experts on the relationship between Vietnam and the World Bank. The achievements that Vietnam has gained are thanks to appropriate development policies of the Party and State, the efforts of hard work and creativity of the people and authorities, as well as to the sympathy and support of international friends, including the World Bank Group.
Keywords: Economic development,Phát triển kinh tế; Vietnam,Việt Nam